LAFAZ DITINJAU DARI SEGI CAKUPANNYA (âÃM - KHÃS - MUTHLAQ - MUQAYYAD) - Sahib, Muhammad Amin (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
Lafaz is an expression to understand a thing. The meaning of lafaz was strongly influenced by anything that followed it.Lafadz could have significant meaning:Ã¢m (general), khÃ¢s (specific), muthlaq (definite) and muqayyad (bound). This article explains how lafadz has a general, specific, definite, and bound meaning to explain the rules / regulations that may affect it. It exposed them by mentioning some opinions and compared them with examples from the Koran and Hadith to find a more clear understanding of the arguments of Syaraâ.